ANALISIS TINGKAT KOMPETENSI LITERASI DIGITAL PADA PELAKU WISATA BERBASIS KEARIFAN LOKAL - Atika Rahma; Nurfitraeny Nasruddin; Haidir Ali; Amelsyah Putri (Institut Agama Islam Negeri Palopo, 2024)
This thesis discusses digital literacy in the tourism sector based on local wisdom. The research aims to determine the level of digital literacy competence of local wisdom-based tourism actors in Palopo City. This research uses a quantitative research design with a descriptive statistical analysis approach. The population in this study is local wisdom-based tourism actors in Palopo City. The sampling technique used is nonprobability sampling with the accidental sampling method, resulting in 35 samples of local wisdom-based tourism actors in Palopo City. Data collection was done by distributing questionnaires directly to the respondents. The results of this study indicate that the level of digital literacy competence of local wisdom-based tourism actors in Palopo City, measured using the UNESCO DLGF Framework (2018), is in the moderate category with an index score of Respondents' ability to operate digital hardware and software (device and software operations) is in the high category (index score of 4.02). Meanwhile, respondents' ability in digital data, information, and content literacy (information and data literacy) is in the moderate category (index score of 3.32), their ability in collaboration and communication through digital technology (communication and collaboration) is in the moderate category (index score of 3.15), their ability in creating and editing digital content (digital content creation) is in the moderate category (index score of 2.97), their ability to protect data, privacy, and digital devices (safety) is in the high category (index score of 3.57), and their ability in digital gap analysis (problem solving) is in the moderate category (index score of 2.85). Thus, local wisdom-based tourism actors in Palopo City excel in two abilities with the highest index scores, namely device and software operations and safety. However, other abilities still need to be improved, especially digital content creation and problem solving with index scores of only 2.97 and 2.85, respectively, to be more active in digitally branding local wisdom tourism objects in Palopo City